Superfluid motion and drag-force cancellation in a fluid of light - Claire Michel (Nature Portfolio, 2018)
Superfluidity of light enables movement without friction or, in optical terms, diffraction. Here, Michel et al. report the detection of the transition to superfluidity in the flow of a fluid of light past an obstacle in a bulk nonlinear crystal and extract the drag force exerted by the fluid of light.